Outcome of Near Miss Cases in a Periurban Hospital - Nazmeen, Summyia; Tasnim, Saria; Ara, Iffat (Journal of Bangladesh College of Physicians and Surgeons, 2018)
A near miss or severe acute maternal morbidity (SAMM) means a woman (in pregnancy /labour/puerperium) who was almost dead but survived. It is often poor, socially excluded women that suffer most. The objective of this study was to explore the outcome of near miss cases admitted in the hospital along with their presentation, socio demographic characteristic and medical and surgical intervention needed. It was a cross sectional study conducted from 1st July 2009 to 31st December 2009 at Institute of Child and Mother Health. Among cases who got admitted in the hospital in moribund condition with pregnancy related complications. Total 91 patients were enrolled consecutively. Data were collected by structured questionnaires. Analysis was done using SPSS program. About 72% of women were at second decade of their lives and 71% of them were from poor socioeconomic condition. About 39% patients did not take any antenatal checkup. A near miss or severe acute maternal morbidity (SAMM) means a woman (in pregnancy /labour/puerperium) who was almost dead but survived. It is often poor, socially excluded women that suffer most. The objective of this study was to explore the outcome of near miss cases admitted in the hospital along with their presentation, socio demographic characteristic and medical and surgical intervention needed. It was a cross sectional study conducted from 1st July 2009 to 31st December 2009 at Institute of Child and Mother Health. Among cases who got admitted in the hospital in moribund condition with pregnancy related complications. Total 91 patients were enrolled consecutively. Data were collected by structured questionnaires. Analysis was done using SPSS program. About 72% of women were at second decade of their lives and 71% of them were from poor socioeconomic condition. About 39% patients did not take any antenatal checkup. J Bangladesh Coll Phys Surg 2018; 36(1): 20-25